The meaning of „nasal grunts” in the NECTE corpus. A preliminary perceptual investigation - Chlébowski, Aurélie (Research in Language, 2016)
This paper reports a perceptual evaluation of the meanings conveyed by the acoustic components of “nasal grunts” (Chlebowski and Ballier 2015), i.e., non-lexical conversational sounds realised with a nasal feature (e.g. <ehm>, <uhhuh>, <mmhm>). This study follows the experimental investigation conducted by Chlebowski and Ballier (2015) on the acoustic components of such sounds in the PVC project (Milroy et al. 1997), which is part of the NECTE corpus (Allen et al. 2007). In accordance with current claims in the literature, they ascribed meanings to these acoustic features, e.g. fall-rises express that the “speaker implies something” (Wells 2006: 27), and verified their validity through an analysis of the context surrounding the “nasal grunts”. Nonetheless, to avoid problems of circularity and ad hoc categories, the present study includes a perceptual evaluation by four participants. To verify the meanings ascribed to the features of “nasal grunts”, three native speakers of American English were recorded in short casual conversations and three perception tests were created using these recordings, with Praat software (Boersma and Weenink 2009). The first two tests aim to check whether different acoustic features: 1) are perceived as different when presented in pairs; 2) can be identified by the participants (as falls or rises) in isolation. The last test aim to determine whether each feature bears the same meaning: 1) in isolation, 2) in a given context, or 3) in scripted conversations likely to trigger the meanings ascribed by Chlebowski and Ballier (2015). Results suggest that acoustic components of “nasal grunts” in Geordie English do convey specific attitudinal meanings, and raise the possibility of a perceptual hierarchy of those components.